Influence of different sports on bone mass in growing girls - Ubago-Guisado, E.; Gómez-Cabello, A.; Sánchez-Sánchez, J.; Garcia-Unanue, J.; Gallardo, L. (Journal of Sports Sciences, 2015)
The aim of this study was to analyse whether there are differences in bone mass in girls playing different sports. Two hundred girls (10.6 ± 1.5 years old, Tanner stages I-III) participated in the study and were divided into groups of 40 (swimmers, soccer players, basketball players, handball players and controls). Bone mineral content and bone mineral density (BMD) (whole body and hip) were measured using dual-energy X-ray absorptiometry. The degree of sexual development was determined using Tanner test, and physical activity habits were recorded through a questionnaire designed ad hoc for this research. Girls were divided by pubertal stage and the type of sport. In the prepubertal group, intertrochanteric BMD was significantly higher in both handball and soccer players compared with the control group (P < 0.05). Furthermore, in the pubertal group, total BMD, mean arms BMD, pelvis BMD, femoral neck BMD, intertrochanteric BMD and Ward`s triangle BMD were significantly higher in soccer and handball players compared with the control group (P < 0.05), and the swimmers showed significantly higher values in the mean arms BMD compared with the control group (P < 0.01). Our data suggest that sport practice during puberty, especially in activities that support the body weight, may be an important factor in achieving a high peak bone mass and improving bone health in girls.